Waqf Management in the Madura Islands: Analysis of the Implementation of PSAK 112 from a Sharia Economic Perspective - Mubarak Mubarak; Dian Berkah; Khairul Jannah (Journal of Waqf and Islamic Economic Philanthropy, 2026)
This study aims to analyze the implementation of the Statement of Financial Accounting Standards (PSAK) 112 on Waqf Accounting at the Majelis Pendayagunaan Wakaf Muhammadiyah (MPWM) Pamekasan and its compliance with Islamic economic law provisions. The research employs a descriptive qualitative method with a case study approach. Primary data were obtained through in-depth interviews and document observation of financial reports, while secondary data were derived from annual reports, regulations, and scholarly literature. The analysis was conducted using content analysis by comparing field practices with PSAK 112 and Islamic legal regulations (Law No. 41/2004 on Waqf, Government Regulation No. 42/2006, and the DSN-MUI fatwas). The findings reveal that MPWM Pamekasan has presented financial statements in accordance with the PSAK 112 format, including the statement of financial position, statement of activities, cash flow statement, and notes to the financial statements. However, gaps remain in the recognition and measurement of waqf assets, particularly in applying fair value and conducting periodic revaluations. Information disclosure has yet to fully include revaluation policies and waqf management risks. From the perspective of Islamic economic law, regulatory compliance exists, yet public transparency remains limited. This study recommends improving asset valuation accuracy, enhancing disclosures, and increasing report transparency to strengthen accountability in waqf management.